Case study research : core skill sets in using 15 genres - Woodside, Arch G. (Emerald Group Publishing Limited, 2016)
Case Study Research: Core Skills in Using 15 Genres examines the processes involved in conducting case research in a number of genres including participant observation, fuzzy set social science, system dynamics, decision systems analysis, forced metaphor elicitation technique, ethnographic decision tree modeling, mapping strategic thinking, the historical method, storytelling research and conversational analysis. The book reviews and applies the best literature on case study methods from a number of disciplines providing a strong rationale for adopting case study research methods alone or in mixed-methods. This fully revised and updated second edition employs a broad and deep coverage of multiple case study research genres to comprehensively explore the topic.
Keywords: Research -- Methodology.; Business & Economics -- Management.; Business & management: study & revision guides.; elektronické knihy; electronic books